“The common people have spoken with a mighty voice”: Regina’s Labour City Councils, 1936–1939 - Brennan, J. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2013)
Working-class political activity at the municipal level in Regina began in 1914 on the initiative of members of the Regina Trades and Labour Council. Early on trade unionists reached out to the city’s middle class, and together they founded a succession of Labour political parties in the 1920s. After 1930 members of the Canadian Brotherhood of Railway Employees also became involved. Success came in 1935, when the Civic Labour League, an informal alliance of social democrats and communists, won the mayoralty and a majority of the aldermanic seats on city council. Labour maintained its hold over City Hall until the end of the decade, but it did not accomplish much. It could not convince the province’s Liberal government to take over full responsibility for the cost of relief or enact a special city charter that would give Regina wider powers (to construct social housing for example) and new sources of revenue. Then in 1939 Labour’s political fortunes shifted dramatically. Accusations of communist influence in the selection of the Labour slate played into the hands of the city’s business community, Regina’s daily newspapers, and the Civic Voters’ Association, which was founded on the eve of the civic election, and Labour suﬀered a crushing defeat.